P3. 15-21 Real-World Experience of First-Line Afatinib Treatment in Patients with EGFR Mutant Advanced Non-Small Cell Lung Cancer. - Chai, Chee Shee; Liam, Chong Kin; Ho, G.; A, Binti Alip; Pang, Y. (Elsevier, 2018)
Background: Published reports of first-line afatinib treatment efficacy, side-effects and resistance mechanism in the real-world setting are lacking.